The Noble Mikalojus Kristupas Chaleckis (Mikołaj Krzystof Chalecki) and His Literary Legacy - Liškevičienė, Jolita (Senoji Lietuvos literatūra, 2015)
The aim of the paper is to introduce the reader to the little-known and poorly researched literary legacy of the noble Mikołaj Krzysztof Chalecki (Lith. Mikalojus Kristupas Chaleckis, c. 1589–1653). It gives a broad description of his biography and origin, his family and foundations provided thus highlighting his personality and his literary legacy in the first half of the seventeenth century. Also, it introduces other individuals connected with him or his works, and discusses the place of the works, which merged literature and art, in the context of the history of literature and art of Lithuania.Two of his works discussed in a greater detail – Allegoriae, albo Kwięcia modł gorących… and Binarius Chalecianus, sive duo manipuli liliorum ... – are attributed to the genres that have not yet been properly researched in Lithuania: to devotional legacy of old literature of the Grand Duchy of Lithuania and to the examples of original Lithuanian emblematic literature. These works do not follow the Jesuit tradition that widely used the emblems; they are a highly individual expression of an intellectual noble, the manner of thinking and its expression that he had brought from Europe. In the late sixteenth-early seventeenth century, reflections on piety became a distinct phenomenon in European literature, which had acquired the attractive form of the emblem. The two (Latin and Polish) versions of Allegoriae containing emblematic woodcuts printed at the Leo Mamonich printing house in Vilnius present Chaleckis as a representative of Western European literature and emblemics of those times, as well as an author of the individual and original expression of the confession of faith in Lithuania.The author of the article updated the time and location of writing of the Latin text of Allegoriae. The first variant of the text was prepared in Latin in Sidra in 1612 and was written (or translated?) in Polish after some time; both were published several years later, in 1618. It is Chaleckis’ only work prepared and published in Polish. It is quite possible that Stanisław Serafin Jagodyński, who devoted himself to literary work, might have contributed to the preparation of the text.Binarius Chalecianus (1642) is the publication which for the first time implemented an original visual form of the Litany of Loreto in the literature of the Grand Duchy of Lithuania along with the founding of the Holy House Loreto of the Holy Virgin Mary in Valkininkai.Mikalojus Kristupas Chaleckis’ works, in which both literary and artistic forms are exploited, are an original manifestation of piety and and example of devotion of a Catholic noble of the Grand Duchy of Lithuania of the early seventeenth century
Keywords: -